Thru‐Hole Epitaxy: A Highway for Controllable and Transferable Epitaxial Growth - Dongsoo Jang; Chulwoo Ahn; Youngjun Lee; Seungjun Lee; Hyunkyu Lee; Donghoi Kim; Yongsun Kim; Ji‐Yong Park; Young‐Kyun Kwon; Jaewu Choi; Chinkyo Kim (Advanced Materials Interfaces, 2023)
Abstract Controllable growth and facile transferability of a crystalline film with desired characteristics, acquired by tuning composition and crystallographic orientation, become highly demanded for advanced flexible devices. Here the desired crystallographic orientations and facile transferability of a crystalline film can be achieved by “thru‐hole epitaxy” in a straightforward and undemanding manner with no limitation on the layer number and polarity of a 2D space layer and the surface characteristics. The crystallographic alignment can be established by the connectedness of the grown material to the substrate through a small net cross‐sectional area of thru‐holes, which also allows the straightforward detachment of the grown material. Thru‐hole epitaxy can be adopted for the realization of advanced flexible devices on large scale with desired crystallographic orientation and facile transferability.